Analysis of Employee Performance in the Regional Secretariat of Sorong District - Astri Wulan Purnamasari; Mahlia Muis; Wardhani Hakim (Hasanuddin Journal of Business Strategy, 2020)
This research was conducted by the author with the aim know employee performance at the Regional Secretariat of Sorong Regency seen in aspects on aspects inputs(input), process (process), outputs (output), outcomes (results), benefits (benefits), and impacts (impact). The research method is a descriptive method with a qualitative approach. Data collection techniques, namely interviews, observation, and documentation using the interactive model. The results of this study indicate the performance of employees at the Regional Secretariat of Sorong Regency is considered to be carried out well, this is indicated by the success of the objectives that have been planned by the Sorong Regency regional government by ensuring all inputs, starting from reliable and competent human resources for all their duties and functions, the existence of adequate facilities and infrastructure and adequacy of the budget. From the main tasks and functions, and work programs can be realized maximally and provide benefits and positive impacts for the needs of community services and also increase regional development. The performance of employees at the Regional Secretariat of Sorong Regency which is considered good is also inseparable from the work process of employees being able to utilize all resources optimally,